Mass Die‐Off Events in Swarming Hyperiid Amphipods: Potential Drivers - Tamar Guy‐Haim; Anastasiia Iakovleva; Viviana Farstey; Ayah Lazar; Khristina Ermak; Arseniy R. Morov (Ecology and Evolution)
ABSTRACT Beach mass stranding events of marine organisms, widely documented worldwide, are triggered by a range of biotic and abiotic environmental factors, often unexplained. Such occurrences among pelagic crustaceans are less frequent, yet not uncommon. Here we studied mass mortality events of hyperiid amphipods—abundant members of pelagic zooplankton, commonly associated with gelatinous organisms. Our study examined consecutive mass die‐off and stranding events of free‐living hyperiids in the Red Sea during 2023 and 2024. We investigated three potential causes: semelparous reproduction, thermal stress, and physical oceanographic conditions. To place our findings in a broader context, we further performed a global review of hyperiid swarming and mass mortality events from scientific literature and a citizen science repository. Morphological and molecular analyses confirmed that the hyperiid species in the die‐off events at the Red Sea was Anchylomera blossevillei (Phrosinidae). The balanced male: female sex ratio (0.99), combined with the absence of gravid or brooding females, led to the rejection of semelparity as a driving factor. The environmental data did not indicate thermally stressful conditions, and no evidence of parasitic infection was found. Nonetheless, previous studies have shown that under weak wind conditions, as measured during the stranding events, coherent cyclonic eddies with diameters of 5–6 km are developed in the northern Gulf of Aqaba, persisting for about a day. These eddies can exceed velocities of 100 cm s−1 and may have facilitated the hyperiid stranding events. Future research should unveil the impacts of such events on marine ecosystems.